Inkjet Printing-Based Immobilization Method for a Single-Step and Homogeneous Competitive Immunoassay in Microchannel Arrays - Kawai, Yuko; Shirai, Akihiro; Kakuta, Masaya; Idegami, Kotaro; Sueyoshi, Kenji; Endo, Tatsuro; Hisamoto, Hideaki (Frontiers in Chemistry, 2020)
In this study, we report an inkjet printing-based method for the immobilization of different reactive analytical reagents on a single microchannel for a single-step and homogeneous solution-based competitive immunoassay. The immunoassay microdevice is composed of a poly(dimethylsiloxane) microchannel that is patterned using inkjet printing by two types of reactive reagents as dissolvable spots, namely, antibody-immobilized graphene oxide and a fluorescently labeled antigen. Since nanoliter-sized droplets of the reagents could be accurately and position-selectively spotted on the microchannel, different reactive reagents were simultaneously immobilized onto the same microchannel, which was difficult to achieve in previously reported capillary-based single-step bioassay devices. In the present study, the positions of the reagent spots and amount of reagent matrix were investigated to demonstrate the stable and reproducible immobilization and a uniform dissolution. Finally, a preliminary application to a single-step immunoassay of C-reactive protein was demonstrated as a proof of concept.